2005
DOI: 10.1002/pbc.20521
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of ventricular function in sickle cell disease: Effect of long‐term erythrocytapheresis

Abstract: Our study demonstrates that patients SCD on LTE have cardiac dysfunction based on elevated LVMPI. This may be a reflection of the global severity of disease. Our findings merit further investigation with serial monitoring of LVMPI on a larger number of patients with SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…1,2 Low haemoglobin levels in sickle cell anemia are associated with an elevated cardiac output at rest, cardiomegaly, and frequently, heart murmurs, due to an increase in stroke volume. 3,4 It has been postulated that excessive work load chronically imposed on heart by the cardiac output, along with the tendency of the sickle cells to occlude vessels in the systemic, pulmonary and coronary circulation during crisis phase may result in LV dysfunction.…”
mentioning
confidence: 99%
“…1,2 Low haemoglobin levels in sickle cell anemia are associated with an elevated cardiac output at rest, cardiomegaly, and frequently, heart murmurs, due to an increase in stroke volume. 3,4 It has been postulated that excessive work load chronically imposed on heart by the cardiac output, along with the tendency of the sickle cells to occlude vessels in the systemic, pulmonary and coronary circulation during crisis phase may result in LV dysfunction.…”
mentioning
confidence: 99%
“…During apheresis, the decrease in the level of calcium ions may cause prolongation of the plateau phase of myocardial depolarization, and this occasionally displays itself as prolongation of the QTc interval on electrocardiogram (Hester et al , 1983; Meikle & Milne, 2000; Laspina et al , 2002; Raj et al , 2005). In case of prolongation of QTc, plasma calcium values (a marker of citrate toxicity at the myocardial level) should be analysed (Roberts et al , 1984; Toyoshima et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[8] Raj AB, Condurache T in their study of 22 patients with SCD found LVDD is more prevalent in severe anemia and it was found to be statistically significant (P = .003). [14] …”
Section: Association Of Lvdd With Agementioning
confidence: 99%